As escolas vocacionais e o terceiro ambiente de Hargreaves - Albino, César [UNESP]; De Lima, Sonia Regina Albano [UNESP] (My University, 2010)
The article refers to an official school experience which was developed in the Brazilian education in the 60's - the vocational schools. These schools enabled an artistic-musical learning experience which would be less technicist and autocratic, contributing in a satisfactory way to the future performing formation of the students. In addition to the historical report, the text refers to the British educator D. Hargreaves, who researched on the importance of the third environment in the musical learning and on the relationship existing between the internal and the external cognitive process. The text is part of the Master or Arts dissertation which is being carried out in the IA-UNESP (Institute of Arts - State of São Paulo University). The musical-theoretical foundations were provided by the ideas of D. Hargreaves, Sigurd Raschèr, Yehudi Menuhi, among others, and by some researchers in the area of education. It is justified on the grounds of the present moment experienced by the musical teaching in face of the approval of Law no 11.769/2008.
The vocational schools and Hargreaves's third environment
Keywords: Hargreaves' third environment; Musical teaching; Vocational schools